“The agenda for the indigenous movement is far-reaching, it goes beyond Reserves”: Interview with Fermín Chimatani Tayori, president of ANECAP - Delgado Pugley, Deborah (2022)
Fermín Chimatani Tayori is an indigenous Harakbut leader from Puerto Luz, Madre de Dios (Perú). He was twice president of the Executor of the Amarakaeri Communal Reserve Administration Contract (ECA Amarakaeri). He is currently president of the National Association of Executors of the Communal Reserves Administration Contract (ANECAP). Recognized by the Peruvian state, Communal Reserves are direct use Protected Natural Areas. These represent an innovative initiative for the coadministration of conservation between indigenous organizations in the Peruvian Amazon and the National Service for Protected Natural Areas (SERNANP). In this interview, Fermín Chimatani Tayori shares his experiences as a key actor in conceptualizing and executing of this process.